2020
DOI: 10.3390/ijerph17124319
|View full text |Cite
|
Sign up to set email alerts
|

Weight Stigmatization and Binge Eating in Asian Americans with Overweight and Obesity

Abstract: Weight stigma and binge eating have been found to be associated in Western populations; however, this relationship is understudied among Asian Americans. The aims of the study were to (1) investigate the prevalence of binge eating and its relationship with experienced weight stigma in higher-weight Asian Americans, and (2) examine whether the level of acculturation moderates this relationship. Data were collected from a cross-sectional study with 166 higher-weight Asian American adults living in North Carolina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 60 publications
0
23
1
Order By: Relevance
“…In addition to the finding regarding the association between weight-related self-stigma and healthy behaviors, an association between experienced weight stigma and unhealthy behaviors has been found. Wu et al [ 12 ] recruited 166 Asian Americans, with most of them being the first generation to understand the association between experienced weight stigma and binge eating behaviors. The participants were defined as overweight according to the body mass index cutoff for Asians (i.e., body mass index > 23 kg/m 2 ).…”
Section: Findings Of the Contributions In The Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the finding regarding the association between weight-related self-stigma and healthy behaviors, an association between experienced weight stigma and unhealthy behaviors has been found. Wu et al [ 12 ] recruited 166 Asian Americans, with most of them being the first generation to understand the association between experienced weight stigma and binge eating behaviors. The participants were defined as overweight according to the body mass index cutoff for Asians (i.e., body mass index > 23 kg/m 2 ).…”
Section: Findings Of the Contributions In The Special Issuementioning
confidence: 99%
“…The participants were defined as overweight according to the body mass index cutoff for Asians (i.e., body mass index > 23 kg/m 2 ). After controlling the effects of racism and general stress, Wu et al [ 12 ] concluded that experienced weight stigma is an independent factor associated with binge eating behaviors for those who may have a weight problem.…”
Section: Findings Of the Contributions In The Special Issuementioning
confidence: 99%
“…A total of 20 studies were included in this review, of which 1 study comprised 4 separate studies [ 29 ], resulting in 23 studies (representing 2231 participants) evaluated in this review. A summary and detailed description of the study characteristics are shown in Table 1 and Multimedia Appendix 3 [ 25 , 26 , 29 - 47 ] and Multimedia Appendix 4 [ 25 , 26 , 29 - 37 , 39 - 47 ]. The chatbot programs included Wakamola [ 30 - 32 ], WaznApp [ 33 ], WeightMentor [ 25 ], SWITCHes [ 34 ], MobileCoach [ 35 ], PathMate2 [ 36 ], and Lark Weight Loss Health Coach AI [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Core functions of the chatbot were to provide personalized weight loss recommendations (20/23, 87%) [ 25 , 26 , 29 - 34 , 37 - 39 , 41 - 46 ] and motivational messages (18/23, 78%) [ 25 , 26 , 29 - 33 , 37 - 39 , 41 - 43 , 45 , 46 ] ( Multimedia Appendix 5 [ 25 , 26 , 29 - 37 , 39 - 47 ]). Only 26% (6/23) studies [ 30 - 32 , 36 , 40 , 43 ] mentioned the use of gamification to enhance user engagement, and 26% (6/23) studies [ 37 , 39 , 40 , 42 , 43 , 45 ] mentioned the use of sentiment analysis to provide emotional support through emotionally appropriate messages ( Multimedia Appendix 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation